Assessing carbamazepine and oxcarbazepine‐associated Stevens‐Johnson syndrome/toxic epidermal necrolysis: Data mining the public version of the FDA adverse event reporting system. Issue 8 (17th May 2021) - Xu, Caibing; Pan, Lingyun; Zhang, Yuxia; Zhang, Jinghua; Sun, Qiuyan; Fang, Wei
Abstract: Aims: Stevens‐Johnson syndrome and toxic epidermal necrolysis are viewed as the most severe drug‐induced types of cutaneous adverse reactions, with high rates of morbidity and mortality. We aimed to examine carbamazepine‐ and oxcarbazepine‐associated Stevens‐Johnson syndrome or toxic epidermal necrolysis, by data mining the US Food and Drug Administration Adverse Event Reporting System (FAERS). Methods: Reports in FAERs were analysed, from the first quarter of 2004 to the last quarter of 2019. Pharmacovigilance tools were employed for the quantitative detection of signals, where a signal represents a drug‐associated adverse event, including the reporting odds ratio, proportional reporting ratio, an information component given by a Bayesian confidence propagation neural network, and the empirical Bayes geometric mean. Results: The total number of reports identified as Stevens‐Johnson syndrome or toxic epidermal necrolysis associated with carbamazepine or oxcarbazepine included in this study was 1231. FAERS reports associated with carbamazepine were 1048, including Stevens‐Johnson syndrome (n = 668) and toxic epidermal necrolysis(n = 380). FAERS reports associated with oxcarbazepine were 183, including 142 Stevens‐Johnson syndrome and 41 toxic epidermal necrolysis reports. The risk for Stevens‐Johnson syndrome is higher than for toxic epidermal necrolysis and carbamazepine is associated with a higher risk than oxcarbazepine. Conclusions: The results of our study are consistent with clinical observations, suggesting the necessity for further clinical research on Stevens‐Johnson syndrome and toxic epidermal necrolysis associated with carbamazepine or oxcarbazepine.